Transferencias de recursos y partidos políticos. Estudio de los municipios mexicanos (Funds transfers and political parties. Study of Mexican municipalities) - Tamez Garza, Silverio; Hinojosa Cruz, Adriana Verónica; Jiménez Zárate, Carlos Augusto (Facultad de Contaduría Pública y Administración U.A.N.L., 2013)
Abstract. In this paper we analyze how much influence the political party with the largest nationwide (Partido Revolucionario Institucional: PRI) in the Congress, specifically the House of Representatives, in the distribution of the Funds of Branch 23: Paving Fund and Sports Spaces for Municipalities, for the year 2010 which is when this fund was created and for the year 2011. The results of our analysis were that there is a positive impact in the influence of the political party with the largest presence in the Chamber of Deputies in the allocation of resources to those municipalities that are governed by mayors from the PRI.